Resposta da comunidade zooplanctônica e efeitos em cascata à predação: uma abordagem experimental. - Silva, Heloisa Santos (2019)
The presence of a predator can play a key role in structuring ecological communities through both predation and their indirect threat. Predation risk in aquatic systems is often assessed by prey by chemical cues, either those released by prey or the predator itself. Through an experimental approach, this study sought to evaluate the influence of a chemical signal or the effective presence of a top predator (omnivorous fish) on the variation in the abundance of zooplankton communities, and if interference from these higher levels occurs, trophic cascade over the protoplankton community. The results showed the ability to induce a chemical signal and the perceived threat of predation of (zooplankton microcrustaceans) by predatory fish (Moenkhausia bonita). The presence of chemical cues made it cause to seek refuge from prey, demonstrating the indirect influence of a piscivore on the structure of a trophic cascade and its impacts on communities of protist ciliates, present at lower levels of a chain.